Digital Transformation In Islamic Pawn Services: User Experiences of Pegadaian Syariah Digital Service at Ahmad Yani Branch, Jember - Dini Wahyuni; Abdul Mun'im (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze customer experiences in using Pegadaian Syariah Digital Service (PSDS) at the Ahmad Yani Branch in Jember within the context of digital transformation in Islamic pawn services. A qualitative research approach was employed, with data collected through interviews, observations, and documentation. The findings indicate that customers respond positively to PSDS due to its ability to improve accessibility, efficiency, and convenience in financial transactions. Through this digital platform, customers are able to access information, monitor transactions, and make payments without visiting branch offices. However, the implementation of this digital service still faces several challenges, including limited internet connectivity, differences in digital literacy levels, occasional technical disruptions, and concerns regarding system reliability. These findings highlight that digital transformation is not merely about technological implementation but also involves changes in customer behavior, interaction patterns, and service expectations. Therefore, the success of digital Islamic pawn services requires continuous improvement in technological infrastructure, enhancement of digital literacy, and sustainable customer support systems that are responsive and reliable